Association Between Attitude Toward Death and Completion of Advance Directives. (December 2016) - Lynn, Theresa; Curtis, Amy; Lagerwey, Mary D.
Advance directives provide health-care instruction for incapacitated individuals and authorize who may make health-care decisions for that individual. Identified factors do not explain all variance related to advance directive completion. This study was an analysis of an association between advance directive completion and death attitudes. Surveys that included the Death Attitude Profile—Revised were completed anonymously. Comparisons of means, chi-square, and logistic regression tests were conducted. Among individuals who did not consider themselves religious, the mean death avoidance attitude scores differed significantly among those with advance directives (mean = 1.93) and those without (mean = 4.05) as did the mean approach acceptance attitude scores of those with advance directives (mean = 5.73) and those without (mean = 3.71). Among individuals who do consider themselves religious, the mean escape acceptance attitude scores differed significantly among those with advance directives (mean = 5.11) and those without (mean = 4.15). The complicated relationships among religiosity, advance directives, and death attitudes warrant further study.